Fostering English as Foreign Language Students’ Autonomy Level in Vocabulary Development - Siti Roki'ah; Sumardi; Suparno (UICELL, 2020)
This research aimed to explore the students' autonomy level in vocabulary development and teachers' role in fostering students' autonomy level. This research explored university students' level of autonomy in English learning and to gain a better understanding of teachers' role in promoting LA in vocabulary development. A qualitative case study design was conducted to analyze the data. The findings showed that the students capable of controlling their learning strategy, motivation, and emotion understood the best condition to study; in this case, the student may control their learning vocabulary capacity, influencing their autonomy level. Furthermore, the teacher's teaching strategy also influenced the student's autonomy level. The more teachers engaged students in the classroom activity, the more they could control their learning strategy, which meant their autonomy level was getting higher. The research's implication is allowing the student to select their preferred method of learning can assist them in increasing their vocabulary. Practical strategies to learn vocabulary must be included to develop learner autonomy because learners' input in the academic context plays a vital role in independent vocabulary learning.